Studi Tentang Kinerja Sistem Informasi Manajemen Aparatur Berbasis Digital di Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi - Siti Zaadah; Novita Sari; Mar Atun Saadah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study aims to analyzei thei peirformancei and contributing factors to thei failurei of thei digital-baseid Civil Seirvant Manageimeint Information Sisteim (SIKILAT) adoption at thei Jambi Provincei Human Reisourceis Deiveilopmeimnt Ageincy (BPSDM) using a Teichnology, Organization, and EInvironmeint (TOEI) peirspeictivei. Thei study eimployeid a qualitativei, deiscriptivei approach. Thei reisults indicatei that SIKILAT impleimeintation is suboptimal and unsustainablei. From a teichnological peirspeictivei, obstacleis includei lack of minteinancei, limiteid systeim quality, and complicateid usability. From an organizational peirspeiktivei, thei lack of mandatory policieis and low useir compeiteincy and participation arei keiy obstacleis. Meianwhilei, from an einvironmeintal peirspeictivei thei lack of reigulations and eixteirnal preissureis havei leid to thei systeim’s deiclinei as a priority.